A simulation based performance evaluation of optical ethernet switch - Dawit Hadush Hailu; Gebrehiwet Gebrekrstos Lema; Gebremichael T. Tesfamariam; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
With the advent of several new cloud radio access network (C-RAN) technologies, today’s networking environment is dramatically altered and is experiencing a rapid transformation. One of the most important is ethernet based C-RAN, in support of which many products such as optical Ethernet switches have recently appeared on the market. This paper presents the performance analysis of such switches with respect to packet loss ratio (PLR), latency and packet delay variation (PDV). We employed the Simula based on discrete event modelling on Simula (DEMOS), a context class for discrete event simulation to simulate a cut-through optical ethernet switch under two types of traffics: high priority (HP) traffic and low priority (LP) traffic. In this way, the paper evaluates the optical Ethernet switch performance quantitatively. The results obtained from the simulator showed that the high quality of service was reflected on HP traffic and the low quality of service in LP traffic. Hence, HP traffic can be used for transporting radio over ethernet (RoE) traffic while LP traffic can used for transporting time insensitive application. It is also found that HP traffic experiences a PDV equals to the duration of maximum sized LP traffic in Optical Ethernet switch.